ANALISIS RESEPSI AKTIVIS ORGANISASI MAHASISWA EKSTRA KAMPUS DI SURABAYA TERHADAP ISU KOMUNISME DALAM FILM SENYAP (Universitas Negeri Surabaya, 2022)
Abstract This study examines about reception and interpretation from the member of extra-campus student organization in Surabaya as an activist against communism issues in post-G30S 1965 incidents on Senyap movies. This issue considered, and still consider as a taboo and sentimental thing to discusses in Indonesia until today. Many organizations or foundations had reconciled the victims of this incident. Unfortunately, it is not well accepted by the government so there are frequent forced dissolution occurs at closed-door discussion on this issue. The methodology of this study is reception analysis which generate data form of informants categories in recepting and interpreting the message which divided into two positions. As follows; 1) Hegemony-dominant, there are two informants who accepted all the message in Senyap movie, 2) Negotiation, there are five informants who accepted, but also refused some point of the message that delivered by Senyap movie. The differences of the messages reception by the informants are coming from Islamic, Christian, Catholic, and Nationalist-based organization. Keywords: communism, post-G30S 1965, reception analysis, senyap movie